Abductive Reasoning and Understanding Science - Orozco, Richard (2020)
In this paper, the author presents the scientific work interpreted from abductive reasoning. In this way, the fallible character of science becomes evident, overcoming its naive views. The author also shows how this vision of science from abductive reasoning is linked to a way of scientific realism. Instead, the vision of science dependent on inductive and deductive reasoning are, according to the author, quite similar and closer an infallible vision of science. To demonstrate this, the type of reality assumed by both Francis Bacon and Karl Popper is presented, which the author defines as a previously organized independent reality. Finally, the author proposes that the understanding of science from abductive reasoning reveals three peculiarities of it: functionality, the closeness between science and technology, and the limited rationality of science.